Daoist Writs and Scriptures as Sacred Beings. Issue 1 (24th June 2019) - Kim, Jihyun
Abstract : The formation and solidification of canonical scriptures in Daoism facilitated the establishment and development of the religious tradition. In particular, medieval Daoism was grounded on a unique conception of writs and scriptures. The Daoist concept of scripture is founded on a belief system in which letters and sounds are particular forms of qi, or the omnipresent "pneuma and energy." Such a way of thinking provides a lead for understanding the Daoist veneration of scriptures and other various practices. The aim of this paper is to explore the characteristics of Daoist canonical scriptures as "sacred beings, " mainly through an investigation of the Daoist perspective on scriptures, scripture-worship, and the relationship between scripture and practice.